Technological standards and emission indicators thermal power plants and boiler houses - M. S. Ivanitskiy (Известия высших учебных заведений: Проблемы энергетики)
RELEVANCE this study is based on the need for the practical implementation of the national state strategy for environmental development, which allows for the functioning of the main sectors of the economy with low greenhouse gas emissions, taking into account global climate change, for a gradual transition to full carbon neutrality. Environmental protection policy in the field of environmental protection is aimed at limiting the entry of greenhouse gas emissions into the atmosphere through the development and improvement of organizational and technological measures. Thus, based on the formed strategy, energy enterprises can participate in conducting an experiment on quotas for emissions of pollutants in order to determine the standards for permissible greenhouse gas emissions into the atmosphere for boiler installations of thermal power plants.PURPOSE. The paper analyzes the legislative framework, regulatory and technical documents and methodological approaches to setting standards and evaluating technological indicators of greenhouse gas emissions into the atmosphere for boiler plants.METHODS. Calculations of carbon dioxide emissions into the atmosphere during the operation of boiler installations of thermal power plants using coal and natural gas as fuel (options) are performed in accordance with methodological recommendations based on balance equations. Mass and specific carbon dioxide emissions have been determined for the most common types of coal and natural gas used at Russian thermal power plants.RESULTS. Taking into account the composition and lower heat of combustion of fuel, input thermal power (50 MW or more) and thermal efficiency indicators of thermal power plants of various types, mass and specific carbon dioxide emissions in terms of a ton of natural and conventional fuel are calculated.CONCLUSION. The obtained research results can be used at energy enterprises and thermal power plants in the development of a program to improve environmental efficiency and justify participation in a state experiment on emission quotas, including a gradual transition to full carbon neutrality of the energy production process.